Spontaneous left main coronary artery dissection complicated with vasospasm - Cátia Costa Oliveira (Permanyer, 2021)
CASE PRESENTATION We present the case of a 36-year-old female (informed consent obtained) with a past medical history of childbirth 2 months before being admitted to the emergency room with signs of chest pain with irradiation to her left arm associated with diaphoresis and dyspnea with 1-hour evolution. The electrocardiogram (ECG) performed did not show any alterations, but the blood test confirmed the presence of increased myocardial necrosis markers (troponin I, 1.9 ng/mL; normal < 0.045 ng/mL). The serial ECGs performed revealed progressive alterations, namely T-wave inversion in leads I, aVL, and V1-V3. The transthoracic echocardiogram showed good systolic left ventricular function without wall motion alterations. The patient underwent a coronary angiography that revealed an image suggestive of intramural hematoma conditioning a diffuse stenosis of the left main (LMCA) and proximal left anterior descending (LAD) coronary arteries (video 1 of the supplementary data; figure 1A). Due to the patient’s high-risk coronary anatomy, it was decided to repeat the coronary angiography 8 days later. However, after cannulating the LMCA (6-Fr JL 3.5), a sudden reduction of the distal LMCA and proximal LAD flow was seen (probable vasospasm) (video 2 of the supplementary data; figure 1B). Consequently, the guidewire was crossed to the...